Propuesta de un Sistema de Gestión Integral de Residuos Sólidos municipales en la ciudad de Tarapoto - Macedo del Águila, Delia Amelia (2010)
Tarapoto's city has a population of 68,295 inhabitants and with a population density of 107.15 hab/km ² (INEI - 2007), with an enormous tourist abundance, where there are located the headquarters of the Provincial Municipality (Corporated town) and diverse state entities of importance, likewise; it is located companies of tourism, agencies of the principal banks of the country, municipal boxes(cash desks), and other financial institutions. There is had the presence of important commercial chains, drugstores and the whole great set of commercial establishments. The problem of the managing of the solid municipal residues in Tarapoto's City, increases in significant form due to the population growth, changes in the levels of consumption, between(among) other factors. The scanty participation of the population in the managing of the residues owes to a great extent for the lack of awareness and concientización environmental. Opposite to this situation there is recommended the application of this system of integral management of solid residues to achieve the efficiency of the same one and for ende the quality of life of the population. The intention of this study is to contribute(pay) in the analysis and offer of solutions to the integral management of solid municipal residues. The present investigation(research) is framed in a field study of descriptive character - evaluativo, where there was realized a diagnosis of the current situation, with the purpose of knowing the weaknesses and critical points of the managing of the solid residues, which allowed to develop the offer of the system that was transforming the weaknesses into strengths(fortresses) to future. The present document of thesis has been structured on the basis of a holistic approach of the problematics, for which with strategic ends(purposes) and of order he(she) contemplates the following steps: First: A preliminary study of office where I compile the existing information as for waste management solid and the principal aspects that were necessary for the analysis of the compilation of solid municipal residues.  I identify topics and concepts that I help us to analyze concepts in the whole process of execution of the work of investigation. I come second: Summary of information and Field analysis, correspondent to the diagnosis of the service of public cleanliness of Tarapoto's city; considering two fundamental Aspects:  Technical Aspects - Operative: That describes the stages of the solid residues from his point of Generation up to his Final Disposition.  Managerial Aspects - Administrative: He understands the information about the Analysis of the Management of the Service, Human, Financial Resources, and Triburios.  Once analyzed the situational diagnosis of the service of public cleanliness of Tarapoto's city, observes that the current service is deficient.  The income collected of the public cleanliness during last four years is minor to the expenditures, number that it constitutes in a financial deficit that has been subsidized by other Items. Third party: Summary and analysis of the information: physical Composition of the solid residues, Determination of the coverage of compilation of solid residues and the Determination of the number of compactadoras necessary for the compilation of the solid residues.  The generation per capita is 1.03 Kg/hab/día, the same one that is bigger than the national average found in 2002 of 0,58 Kg./hab./día, with one physical caracterización of solid residues that can be recovered for his commercialization, calculation of the number of compactadoras that are necessary for the compilation of solid municipal residues of the city, giving like proved the requirement of 08 compactadoras with a capacity of 15 m3. And the calculations realized of the coverage of compilation it is 75,69 %, staying a deficit of 24,31 %. Quarter: I realize and analyze surveys to determine if the municipal workers, students of the secondary level and the population, agree or reject a system of integral management of solid municipal residues, in Tarapoto's city.  The results brought a high percentage of acceptance to the System of Integral Management of Solid Municipal Residues, in spite of the fact that the polled ones it does not have major knowledge on the topic. I conscript: In the Formulation of a system of integral management of solid municipal residues in Tarapoto's city, it is considered to be two basic Actions, which allow that the present document should support a functional structure and especially technical. Action 01: Stages of the System of Integral Management of the Solid Municipal Residues, from the Levels of Intervention in Tarapoto's city. Action 02: Efficient Administrative Management. The result of this Thesis is to have achieved the acceptance of the local government, student population and the population, since these actors are indispensable in order that this system works, achieving that the institutional management is efficient in this service.